Multi-response optimization of rhamnolipid production using grey rational analysis in Taguchi method - Zulfiqar Ali Raza; Naseer Ahmad; Shahid Kamal (Biotechnology Reports, 2014)
The present paper envisages the multi-response optimization of certain process parameters like total sugars concentration, C/N ratio and incubation time on rhamnolipid yield, surface tension reduction, biomass formation and substrate utilization, in rhamnolipid production by a Pseudomonas aeruginosa mutant strain grown on clarified blackstrap molasses, under L9 orthogonal array in Taguchi design. The results have been analyzed by using grey relational analysis for the identification of an optimum level of process parameters. The validity of the results was checked though confirmation experiment, under grey relational analysis. Subsequently, the rhamnolipid yield improved from 1.45 to 1.50 g/L, substrate utilization reduced from 26 to 14% (w/v) and lesser biomass was formed. Moreover, the volumetric productivity of the process improved from 0.0086 to 0.0208 g/L/h by 142%. Furthermore, using analysis of variance method, significant contributions of process parameters were determined.